Effects of Continuous Straw Return on Soil Nutrients and Microbial Community Structure of Paddy Fields in Northeast China - Juntao Ma; Qiuju Wang; Jiahe Zou (Agronomy)
Albic soil, which is generally oligotrophic, is a typical low-yield soil widely distributed in China. It is still unclear how to effectively improve soil fertility and strengthen the sustainable development of agricultural cultivation. For this purpose, 8-year field experiments were performed to determine the effects of continuous rice straw return on soil nutrient characteristics, yield, and the soil microbial community. Straw incorporation into albic soil significantly contributed to nutrient accumulation, containing alkali-hydrolysed nitrogen, available phosphorus, available potassium, and total organic carbon, thereby increasing rice yield. The number of spikelets per panicle increased from 93.96 to 97.58, and the grain filling value increased from 88.11 to 91.44%. Additionally, rice yield increased over the 8 consecutive years of straw return, and the rice yield of straw return treatments ranged from 10,048.27 to 10,605.18 kg/ha. High-throughput sequencing and classification revealed that the composition of bacterial and fungal communities was similar among treatments, but there were significant differences in species abundance, which was associated with lignocellulose degradation. Overall, the continuous return of straw, a native organic material, is a promising approach for soil amendment, with resource-saving and environmentally friendly characteristics.